(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: This study examines the role of critical thinking and problem-solving in education and the workforce, analyzing existing literature on the development of these skills. It highlights the importance of these competencies for personal, academic, and professional success in the 21st century. The study emphasizes the gaps in current educational approaches and proposes strategies to enhance the teaching and assessment of critical thinking and problem-solving skills. The findings underscore the need for more innovative teaching methods and a shift from memorization-based learning to skills-based learning in order to equip students with the tools they need to succeed in a rapidly changing world.